Analisis Bisnis Kuliner Menggunakan Marketplace Dalam Peningkatan Penjualan Dan Kemajuan Usaha (Studi Kasus Martabak Den Bagoes Jl. AR. Hakim Medan Kec. Medan Area) - Dimas Pratama; Tri Inda Fadhila Rahma; Wahyu Syarvina (Jurnal Manajemen Akuntansi (JUMSI), 2023)
E-Commerce ( Electronic Commerce) is part of E-Business. ECommerce is the activity of selling, buying, marketing products (goods or services) by utilizing telecommunications networks such as the internet, television or computer networks. Lots of food delivery coming up. Online support today has a big impact on business people. This is evident amaraknya increasingly massive online applications open business opportunities. Including the Shopee Platform introducing Shopee Food, Go-Food and Grab-Food Features. Shopee Food, Go-Food and Grab-Food are food and beverage delivery services. Shopee Food is now much in demand by the public because it offers many promos, discounts, cashback and free shipping features. Many MSMEs are now opening businesses through ShopeeFood because they see business opportunities. The research methodology used is a qualitative approach using mixed methods or mixed methods with the type of case study research. Data collection was conducted by interview techniques, questionnaires and documentation according to the needs of researchers. Data analysis was done by qualitative descriptive analysis and quantitative descriptive analysis. The results obtained are the analysis of the use of ShopeeFood, GoFood and GrabFood in increasing sales and the progress of the culinary business clearly has a positive impact on culinary business actors who join the application and become partners. Culinary entrepreneurs who join the application on average express their satisfaction since joining the application in addition to having an impact in increasing sales, promoting products sold without spending a budget, facilitating transactions, marketing products even without a kitchen and even one of the respondents only uses a cart as a sales stall. The level of sales of culinary businesses in Medan Area all business actors experienced an increase in sales after joining and becoming partners of ShopeeFood, GrabFood and Go-Food even one of the entrepreneurs in the village experienced a significant increase to exceed 100%. martabak den Bagoes culinary business can feel an increase in sales by joining Go-Food, Shopee Food and also Grab-Food because more buyers come to buy through the marketplace. The entrepreneur also said that getting a positive impact researchers can conclude that both culinary business ventures felt the impact after joining Go-Food, ShopeeFood and GrabFood. The impact felt by the culinary business above is a considerable increase in sales can help.